Criteria for Evaluation and Planning of Science Foundation Activity - Glisin, Fedor F.; Kaluzhnyi, Vladimir V.; Melnik, Pavel B.; Shchepanskiy, Sergey B. (International Review of Management and Marketing, 2016)
The growing role of S&T funds as one of the important mechanisms for financing science results in necessity to improve methods for evaluating and planning activities of such funds. In this paper we identified some indicators of scientific activity based on statistical data analysis. On our opinion these indicators should be taken into account for evaluation and planning of R&D activities, in particular, regarding S&T funds. One of the key indicator, which determines pace of scientific development is GERD per one researcher. Accelerated development of science, which manifests itself in a significant increase in its effectiveness. At the same time, it is sufficient to keep the magnitude in order to achieve high values of performance and efficiency of scientific activity if management of financial flows is enough efficient. If each researcher publishes approximately 1 work in two years, it will be enough to ensure the quality and relevance of scientific publications. Key words: corrector, moderator, tutor, subject teacher, meta-competence. JEL Classifications: I22; I20; I23